Conceptualizing Geosexual Archetypes: Mapping the Sexual Travels and Egocentric Sexual Networks of Gay and Bisexual Men in Toronto, Canada. Issue 6 (June 2018) - Gesink, Dionne; Wang, Susan; Guimond, Tim; Kimura, Lauren; Connell, James; Salway, Travis; Gilbert, Mark; Mishra, Sharmistha; Tan, Darrell; Burchell, Ann N.; Brennan, David J.; Logie, Carmen H.; et al.
Abstract : Background: There are complex, synergistic, and persistent sexually transmitted infection (STI) epidemics affecting gay, bisexual and other men who have sex with men (gbMSM) in every major urban centre across North America. We explored the spatial architecture of egocentric sexual networks for gbMSM in Toronto, Canada. Methods: Our integrative mixed methods study included in-depth interviews with 31 gbMSM between May and July 2016. During interviews, participants mapped their egocentric sexual network for the preceding 3 months geographically. At the end, a self-administered survey was used to collect sociodemographic characteristics, online technology use, and STI testing and history. Results: We identified 6 geosexual archetypes: hosters, house-callers, privates, rovers, travellers, and geoflexibles . Hosters always, or almost always (≥80%), hosted sex at their home. House-callers always, or almost always (≥80%), had sex at their partner's home. Rovers always or almost always (≥80%) had sex at public venues (eg, bath houses, sex clubs) and other public spaces (eg, parks, cruising sites). Privates had sex in private—their own home or their partner's (part hoster, part house-caller ). Travellers had sex away from their home, either at a partner's home or some other venue or public space (part house-caller, part rover ). Geoflexibles had sex in a variety of locations—their home, their partner's home, or public venues. All hosters and rovers, and to a lesser extent, geoflexibles, reported a history of syphilis and human immunodeficiency virus. Conclusions: Prioritizing interventions to hosters, rovers, and geoflexibles may have an important impact on reducing STI transmission. Abstract : Six geosexual archetypes were identified: hosters, house-callers, rovers, privates, travellers, and geoflexibles, each with different characteristic profiles. Prioritizing interventions to hosters, rovers, and geoflexibles may reduce sexually transmitted infection transmission.Supplemental digital content is available in the text.